Development of the TOPSIS–PrOPPAGA COMPOSITE INDEX (ICTP) for decision support in the selection process of bovine supplementation - Santana, Nailhane Rodrigues Carvalho; Tahimi, Abdeladhim; Sarmento, Francisco Jácome; Cassettari, Eder Costa; Duarte, Armando Dias (Brazilian Journal of Production Engineering, 2025)
Climate change resulting from unsustainable practices affects biomes and compromises human and animal health. This study proposes the development of the TOPSIS-PrOPPAGA Composite Index (ICTP) as a tool to support decision-making in the selection of bovine supplements during periods of water scarcity. The methodology integrates the TOPSIS method, which assesses the proximity of alternatives to the ideal solution, and PrOPPAGA, which normalizes the criteria based on Gaussian assumptions. The study was developed on a medium-sized farm in Wanderley/BA, considering criteria such as cost, palatability, availability, nutritional value and delivery time. The ICTP demonstrated that alternative A2 was the most indicated by both methods. The study demonstrates that the integrated approach can reduce biases, increase the robustness of decisions and adapt to different agricultural contexts.
Keywords: PROPPAGA; Water scarcity; Decision-making